PENGEMBANGAN LITERASI AWAL PADA PESERTA DIDIK EARLY LITERACY DEVELOPMENT IN STUDENTS - NAHDIAH NAHDIAH; Ali Rachman; Ririanti Rachmayanie (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The researcher aims to quantitatively analyze the relationship between parenting patterns, parental involvement, and language development on early childhood literacy. Data were taken through observation and questionnaires using valid and reliable instruments based on Pearson's Product Moment and Cronbach's Alpha tests. A total of 197 parents and teachers of the Lembayung Pagi Group Kindergarten, South Banjarmasin District participated in this study. The data were analyzed using the classical assumption test consisting of multicollinearity test, heteroscedasticity test, autocorrelation test, normality test, and linearity test before testing the hypothesis. The researcher used multiple linear regression test, F test, partial regression test, coefficient of determination test, and path analysis to test the hypothesis. The results of the analysis showed a significant relationship (1) parenting to literacy; (2) parental involvement in literacy; (3) language development towards literacy; (3) parental involvement in language development; and (4) parenting, parental involvement, language development together for early childhood literacy. The researcher also found that there was no relationship (1) parenting style to children's language development; (2) parenting through language development on children's literacy; and (3) parental involvement through language development towards early childhood literacy. This study only focuses on examining the relationship between the variables that have been described, does not examine how far these factors affect the development of children's literacy abilities. In addition, this study also still cannot explain several variables related to children's literacy which are known through regression testing)